Implementasi Sistem Rekam Medis Pasien untuk kemudahan Laporan Riwayat Medis pada Yayasan Bagja Waluya - Muhamad Miftahudin; Adiat Pariddudin; Anggra Triawan; Fahmi Arnes; FR Dwi Febriantoro (LP3M Universitas Binaniaga Indonesia, 2025)
This community service activity aims to improve the competence of lecturers and students in applying their knowledge in the field of information technology taught in lectures and daily teaching. One of the real implementations carried out is building an Electronic Medical Record (EMR) system in recording the medical status of patients at the Bagja Waluya Foundation. The main problem faced by partners is in recording the assessment of patients who are being treated still using paper. Where recording is done when the patient is first admitted as an inpatient until the fifth day, or commonly referred to as the patient observation stage. Then for the next recording is only done for certain cases. When needed for the next assessment, officers often have difficulty in searching for previous medical record data. Therefore, this electronic medical record system is expected to be a solution to the above problems. The target output of this activity is an application that can help medical officers in recording patient medical records so that it makes it easier for officers to search for patient data, in addition, data stored electronically has a longer retention period so that it will be easy to use for any number of years. In addition, the output of this activity is the formation of reports and journals of community service. The method of implementing the service includes System needs analysis, system design, system development, socialization and training to foundation officers and implementation. The several processes carried out in the Analysis, socialization, training and implementation stages require a relatively long time because it requires adjustment and habituation from officers and users